A chip-integrated Brillouin-based optical memory - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (2017 Opto-Electronics and Communications Conference, OECC 2017 and Photonics Global Conference, PGC 2017, 2017)
Storing and delaying optical signals is key for next generation networks and computing architectures that harness Integrated optics to solve major challenges such as operational bandwidth, capacity and energy efficiency. However, the speed of light, that provides fast data transmission over long distances, becomes a challenge in integrated circuits if one needs to synchronize, reroute, buffer or process data. Therefore, a fast chip-integrated optical buffer is required. Here, we show an approach based on a coherent transfer of information from optical signals to acoustic phonons in a planar integrated circuit. We demonstrate a GHz bandwidth and the compatibility with coherent communication schemes based on amplitude and phase encoding. Furthermore, we show the possibility of advanced on-chip signal processing schemes, such as non-reciprocal light storage.
CRIS-Team Scopus Importer:2021-06-29
Keywords: (070.4340) Nonlinear optical signal processing; (190.0190) Nonlinear optics; (200.4490) Optical buffers; (290.5900) Scattering; stimulated Brillouin